2007
DOI: 10.1007/s00027-007-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and cycling of dimethylsulfide, dimethylsulfoniopropionate, and dimethylsulfoxide during spring and early summer in the Southern Ocean south of New Zealand

Abstract: Concentrations of total dimethylsulfoniopropionate (DMSPt) and its degradation products, dissolved dimethylsulfide (DMS) and dimethylsulfoxide (DMSOd), were measured in surface waters along three transects between 49 to 768S latitude (November 2003& 2005 and December 2004 in the New Zealand sector of the Southern Ocean. Most water samples were collected from the ships underway pump system, and concentrations of DMSPt, DMS and DMSOd obtained with this method showed excellent agreement with Niskin bottle-collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
8
46
1
Order By: Relevance
“…The contact between DMSP that is freshly released from algal cells in response to the hypo-osmotic shock and DMSP-lyase can then produce DMS within the ice matrix. In addition to this issue, Kiene et al (2007) recently reported that the acidification technique failed to preserve DMSP in seawater samples in presence of Phaeocystis sp., which is often found in Antarctic sea ice algal assemblages. DMSP-lyases in Phaeocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The contact between DMSP that is freshly released from algal cells in response to the hypo-osmotic shock and DMSP-lyase can then produce DMS within the ice matrix. In addition to this issue, Kiene et al (2007) recently reported that the acidification technique failed to preserve DMSP in seawater samples in presence of Phaeocystis sp., which is often found in Antarctic sea ice algal assemblages. DMSP-lyases in Phaeocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…DMSP p was calculated as the difference between DMSP t and DMSP d . A recent study (Kiene et al 2007) has noted that DMSP t can be underestimated when colonial Phaeocystis sp. is present in samples preserved using the Kiene & Slezak (2006) method.…”
Section: Methodsmentioning
confidence: 99%
“…Before running samples, tests with standard solutions (up to 26 mM) of DMS (Sigma-Aldrich, Steinheim, Germany) in methanol showed that there was no quenching effect of methanol on the sulfur signal. Because we did not measure residual DMS, we cannot exclude DMSP lyase activity during sample processing, [40] or incomplete oxidation of DMS to DMSO. Thus, residual DMS might have been quantified as DMSP by our method.…”
Section: Determination Of Dmsp and Symbiodinium Abundances In Coral Tmentioning
confidence: 99%